STABILISASI BEKATUL DALAM UPAYA PEMANFAATANNYA SEBAGAI PANGAN FUNGSIONAL - Ni Made Ayuk Puspita Dewi; I Ketut Suter; I Wayan Rai Widarta (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2012)
Rice bran has a high fat content so prone to rancidity. Therefore, it is necessary toinactivate lipase stabilization process which is the cause of rancidity. Factors affecting therice bran stabilization is temperature and time. Appropriate stabilization method canminimize the damage as well as bioactive components of rice bran lipase inactivatesimultaneously. Bran stabilization at low temperature (100 ° C) within a longer time (15min) was able to inactivate lipase contained in the bran and maintain the composition ofbioactive components and antioxidant activity of rice bran